Between Flexibility and Discrimination Against Workers’ Rights: Comparing Outsourcing Protection Policies in Indonesia and the Philippines - Aluna Putri Sagina; Gusnaeni Bachtiar; Aluna Putri Sagita; Zhairah Zulaeyka Imran (University of Jember, Indonesia, 2025)
The practice of outsourcing in Indonesia continues to grow in line with high unemployment rates and demands for labour market flexibility. However, weak legal protection for outsourced workers has led to uncertainty regarding employment status, inadequate wages, and disparities in treatment between permanent and outsourced workers. This situation requires urgent review, given that outsourcing practices in the field often do not comply with applicable laws. Although regulations only allow outsourcing for certain types of work, in reality many companies take advantage of it extensively because of cheaper labour costs and the absence of job security. In this context, it is important to compare Indonesian regulations with those of the Philippines, as the Philippines has a more assertive approach to protecting outsourced workers, including a ban on labour-only contracting and the application of strict institutional standards. This study uses a normative juridical method, with a comparative approach and literature review to analyse the legal frameworks of both countries. The results show that the Philippines has succeeded in creating a more equitable outsourcing system through consistent regulations and strong supervision for worker protection. In contrast, Indonesia still faces inconsistencies in the implementation of regulations, which has led to discriminatory treatment of outsourced workers. Therefore, this study recommends strengthening institutional coordination, effective law enforcement, and vocational education reform as part of a more equitable and sustainable labour reform strategy.